A adoção do adágio do in dubio pro societate na decisão de pronúncia : (in)constitucionalidade e (in)convencionalidade - Dias, Paulo Thiago Fernandes (2016)
This dissertation, linked to the Contemporary Legal and Criminal Systems line of research of the Graduate Program in Criminal Sciences stricto sensu of the Faculty of Law, is an expansive interdisciplinary, historical and in-depth study, concerning the unconstitutionality and unconventionality of how the adage in dubio pro societate incides into the judicial order, as a form of solving legal doubts as to the sufficiency of evidence as to criminal authorship and proof of materiality. Based on hermeneutical discussions, we seek to examine the decision-making act, notably in judicial analysis of the evidence produced by the parties. In this sense, the study found that such judicial protagonism, rather than providing fundamental rights protection, functions in fact, as a reminder of the inquisitorial culture to which the of Criminal Process Code of 1941 and much of the legal institutions that followed are linked. The adoption of the referred to adage as a decision-making standard for the solution of legal questions, violates the rule in dubio pro reo, or the presumption of innocence and human dignity, to the extent that it submits a person to trial, despite no certainty as to the minimum requirements for the delivery of the verdict. Finally, under the new Constitutional order established in 1988, and opening rules provided by paragraph 2 and paragraph 3 of Article 5, of the Federal Constitution, it is necessary to exercise conventional jurisdictional control of normative or judicial acts especially in the course of criminal proceedings. All of this occurs, within the continuing process of human rights internationalization of which Brazil is part of. Through a brief review, the study shows that despite all of the internal and external regulatory efforts to secure human rights, the Brazilian Judiciary, through its Superior Courts, has both systematically and massively been removing the presumption of innocence, in order to consecrate an incompatible adage to the founding values of the Republic.